The Evaluation of Calcium Score Validity in the Diagnosis of Patients with Coronary Artery Disease by Using CT Angiography - Saleh, Anmar Zaki; AL-Mashat, Emad; Ibrahim, Ibrahim Tareq; Fadil, Sabah Mousa (Diyala Journal of Medicine, 2019)
Background: Coronary artery disease is one of important diseases as in many cases ends up with death. Among many types of coronary artery disease is the lipoprotein plaque deposition on the artery wall. Many reports appeared in the literature concerning the causes, investigation, and treatment of the coronary artery disease. As computed tomography scanners were developed, a new non-invasive procedure was introduced using the calcium present in the plaque as an indicator for the amount of plaque in the coronary artery. Objective: To investigate the validity of the calcium score in the diagnosis of coronary artery disease, and also to find the relation between calcium score with calcification and plaque. Patients and methods: Sixty one patients 40 were men and 21 were women evaluated for calcium score. They had symptoms of chest pain and were subjected to electro cardio gram examination to determine their eligibility for computed tomography angiography to investigate the coronary calcification as a marker of atherosclerosis. The history of diseases including hypertension and diabetes were recorded and check renal function test. Anthropometric measurements and the level of fasting lipid profile for patients and normal subjects were tasted. Patients were advised to come fasting prior to the examination. They have been given Beta blocker to reduce the heart rate in the range of 55-65 beats/min. Contrast medium was injected IV by means of injector immediately before scanning. Results: Results revel that not all patients suffering from chest pain with electro cardio gram changes show high calcium score; on the other hand patients with high calcium score they have an increased plaque in their coronary artery. At low calcium score calcium score (0-100), cholesterol, triglyceride and high density lipoprotein are generally inversely proportional with calcium score with the exception of LDL remains virtually unchanged throughout the whole range of calcium score (0 > 300) as appear in the figures . While at high calcium score concentration (>300) lipoproteins are directly proportional with calcium score in contrast with high density lipoprotein which is inversely proportional with calcium Score.